Digestate biochar effects on soil Pb bioaccessibility, crop Pb concentrations, and human health risk in urban vegetable agroecosystems - Jennifer Newell; Rory Doherty; Gary Lyons; Siobhan F. Cox (Environmental Geochemistry and Health, 2026)

A laboratory study of chemicals in nail products and exposure assessment using USEtox - Lei Huang; Tiglath Moradkhan; Efrem Neuwirth; Jennifer Branyan; Abigail Noble; Wayne Halozan; Lan Wang; Sayaka Takaku-Pugh; Christine Papagni; Anne-Cooper Doherty (Science of The Total Environment, 2026)

Planktic foraminifera record the succession of anaerobic metabolisms in particle microenvironments across a pelagic oxygen gradient - Shannon C. Doherty; Catherine V. Davis; Jennifer S. Fehrenbacher (Geochimica et Cosmochimica Acta, 2025)

Accuracy of patient race and ethnicity data in a central cancer registry - Rachel R. Codden; Carol Sweeney; Blessing S. Ofori-Atta; Kimberly A. Herget; Kacey Wigren; Sandra Edwards; Marjorie E. Carter; Rachel D. McCarty; Mia Hashibe; Jennifer A. Doherty; Morgan M. Millar (Cancer Causes & Control, 2024)

Trace element composition of modern planktic foraminifera from an oxygen minimum zone: Potential proxies for an enigmatic environment - Catherine V. Davis; Shannon Doherty; Jennifer Fehrenbacher; Karen Wishner (Frontiers in Marine Science, 2023)
Oxygen limited marine environments, such as oxygen minimum zones, are of profound importance for global nutrient cycling and vertical habitat availability. While it is understood that the extent and intensity of oxygen minimum zones are responsive to climate, the limited suite of viable proxies for low oxygen pelagic environments continues to pose a real barrier for paleoclimate interpretations. Here we investigate the proxy potential of an array of trace element (Mg, Mn, Zn, and Sr) to Ca ratios from the shells of Globorotaloides hexagonus , a planktic foraminifer endemic to tropical through temperate oxygen minimum zones. A species-specific relationship between Mg/Ca and temperature is proposed for quantitative reconstruction of oxygen minimum zone paleotemperatures. Both Mn/Ca and Zn/Ca ratios vary with oxygen concentration and could be useful for reconstructing G. hexagonus habitat where the primary signal can be d\istinguished from diagenetic overprinting. Finally, a robust correlation between Sr/Ca ratios and dissolved oxygen demonstrates a role for Sr as an indicator of oxygen minimum zone intensity, potentially via foraminiferal growth rate. The analysis of these relatively conventional trace element ratios in the shells of an oxygen minimum zone species has tremendous potential to facilitate multiproxy reconstructions from this enigmatic environment.

Mapping cortical disease-burden at individual-level in frontotemporal dementia: implications for clinical care and pharmacological trials - Mary Clare McKenna; Marlene Tahedl; Jasmin Lope; Rangariroyashe H. Chipika; Stacey Li Hi Shing; Mark A. Doherty; Jennifer C. Hengeveld; Alice Vajda; Russell L. McLaughlin; Orla Hardiman; Siobhan Hutchinson; Peter Bede (Brain Imaging and Behavior, 2022)
Imaging studies of FTD typically present group-level statistics between large cohorts of genetically, molecularly or clinically stratified patients. Group-level statistics are indispensable to appraise unifying radiological traits and describe genotype-associated signatures in academic studies. However, in a clinical setting, the primary objective is the meaningful interpretation of imaging data from individual patients to assist diagnostic classification, inform prognosis, and enable the assessment of progressive changes compared to baseline scans. In an attempt to address the pragmatic demands of clinical imaging, a prospective computational neuroimaging study was undertaken in a cohort of patients across the spectrum of FTD phenotypes. Cortical changes were evaluated in a dual pipeline, using standard cortical thickness analyses and an individualised, z-score based approach to characterise subject-level disease burden. Phenotype-specific patterns of cortical atrophy were readily detected with both methodological approaches. Consistent with their clinical profiles, patients with bvFTD exhibited orbitofrontal, cingulate and dorsolateral prefrontal atrophy. Patients with ALS-FTD displayed precentral gyrus involvement, nfvPPA patients showed widespread cortical degeneration including insular and opercular regions and patients with svPPA exhibited relatively focal anterior temporal lobe atrophy. Cortical atrophy patterns were reliably detected in single individuals, and these maps were consistent with the clinical categorisation. Our preliminary data indicate that standard T1-weighted structural data from single patients may be utilised to generate maps of cortical atrophy. While the computational interpretation of single scans is challenging, it offers unrivalled insights compared to visual inspection. The quantitative evaluation of individual MRI data may aid diagnostic classification, clinical decision making, and assessing longitudinal changes.

Ethnicity, socioeconomic status, income inequality, and colorectal cancer outcomes: evidence from the 4C2 collaboration - Cathy J. Bradley; Amy Anderson-Mellies; Evelinn A. Borrayo; Jennifer Anne Doherty; Omar A. Escontrías; David O. Garcia; Shiraz I. Mishra; Andrew L. Sussman; Cynthia A. Thomson; David W. Wetter; Linda S. Cook (Cancer Causes & Control, 2022)

Pre-diagnosis neutrophil-to-lymphocyte ratio and mortality in individuals who develop lung cancer - Laurie Grieshober; Stefan Graw; Matt J. Barnett; Gary E. Goodman; Chu Chen; Devin C. Koestler; Carmen J. Marsit; Jennifer A. Doherty (Cancer Causes & Control, 2021)
Purpose The neutrophil-to-lymphocyte ratio (NLR) is a marker of systemic inflammation that has been reported to be associated with survival after chronic disease diagnoses, including lung cancer. We hypothesized that the inflammatory profile reflected by pre-diagnosis NLR, rather than the well-studied pre-treatment NLR at diagnosis, may be associated with increased mortality after lung cancer is diagnosed in high-risk heavy smokers. Methods We examined associations between pre-diagnosis methylation-derived NLR (mdNLR) and lung cancer-specific and all-cause mortality in 279 non-small lung cancer (NSCLC) and 81 small cell lung cancer (SCLC) cases from the β-Carotene and Retinol Efficacy Trial (CARET). Cox proportional hazards models were adjusted for age, sex, smoking status, pack years, and time between blood draw and diagnosis, and stratified by stage of disease. Models were run separately by histotype. Results Among SCLC cases, those with pre-diagnosis mdNLR in the highest quartile had 2.5-fold increased mortality compared to those in the lowest quartile. For each unit increase in pre-diagnosis mdNLR, we observed 22–23% increased mortality (SCLC-specific hazard ratio [HR] = 1.23, 95% confidence interval [CI]: 1.02, 1.48; all-cause HR = 1.22, 95% CI 1.01, 1.46). SCLC associations were strongest for current smokers at blood draw (Interaction P s = 0.03). Increasing mdNLR was not associated with mortality among NSCLC overall, nor within adenocarcinoma ( N = 148) or squamous cell carcinoma ( N = 115) case groups. Conclusion Our findings suggest that increased mdNLR, representing a systemic inflammatory profile on average 4.5 years before a SCLC diagnosis, may be associated with mortality in heavy smokers who go on to develop SCLC but not NSCLC.

Extra-motor cerebral changes and manifestations in primary lateral sclerosis - Eoin Finegan; Stacey Li Hi Shing; Rangariroyashe H. Chipika; Kai Ming Chang; Mary Clare McKenna; Mark A. Doherty; Jennifer C. Hengeveld; Alice Vajda; Niall Pender; Colette Donaghy; Siobhan Hutchinson; Russell L. McLaughlin; et al. (Brain Imaging and Behavior, 2021)

Chronic kidney disease of unknown origin is associated with environmental urbanisation in Belfast, UK - Jennifer M. McKinley; Ute Mueller; Peter M. Atkinson; Ulrich Ofterdinger; Siobhan F. Cox; Rory Doherty; Damian Fogarty; J. J. Egozcue; V. Pawlowsky-Glahn (Environmental Geochemistry and Health, 2021)
Chronic kidney disease (CKD), a collective term for many causes of progressive renal failure, is increasing worldwide due to ageing, obesity and diabetes. However, these factors cannot explain the many environmental clusters of renal disease that are known to occur globally. This study uses data from the UK Renal Registry (UKRR) including CKD of uncertain aetiology (CKDu) to investigate environmental factors in Belfast, UK. Urbanisation has been reported to have an increasing impact on soils. Using an urban soil geochemistry database of elemental concentrations of potentially toxic elements (PTEs), we investigated the association of the standardised incidence rates (SIRs) of both CKD and CKD of uncertain aetiology (CKDu) with environmental factors (PTEs), controlling for social deprivation. A compositional data analysis approach was used through balances (a special class of log contrasts) to identify elemental balances associated with CKDu. A statistically significant relationship was observed between CKD with the social deprivation measures of employment, income and education (significance levels of 0.001, 0.01 and 0.001, respectively), which have been used as a proxy for socio-economic factors such as smoking. Using three alternative regression methods (linear, generalised linear and Tweedie models), the elemental balances of Cr/Ni and As/Mo were found to produce the largest correlation with CKDu. Geogenic and atmospheric pollution deposition, traffic and brake wear emissions have been cited as sources for these PTEs which have been linked to kidney damage. This research, thus, sheds light on the increasing global burden of CKD and, in particular, the environmental and anthropogenic factors that may be linked to CKDu, particularly environmental PTEs linked to urbanisation.

Joint exposure to smoking, excessive weight, and physical inactivity and survival of ovarian cancer patients, evidence from the Ovarian Cancer Association Consortium - Albina N. Minlikeeva; Rikki Cannioto; Allan Jensen; Susanne K. Kjaer; Susan J. Jordan; Brenda Diergaarde; J. Brian Szender; Kunle Odunsi; Hani Almohanna; Paul Mayor; Kirsten Starbuck; Emese Zsiros; et al. (Cancer Causes & Control, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

The essential Drosophila CLAMP protein differentially regulates non-coding roX RNAs in male and females - Jennifer A. Urban; Caroline A. Doherty; William T. Jordan; Jacob E. Bliss; Jessica Feng; Marcela M. Soruco; Leila E. Rieder; Maria A. Tsiarli; Erica N. Larschan (Chromosome Research, 2017)

Epidemiologic paradigms for progress in ovarian cancer research - Shelley S. Tworoger; Jennifer Anne Doherty (Cancer Causes & Control, 2017)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Comparison of methods used to calculate typical threshold values for potentially toxic elements in soil - Rebekka McIlwaine; Siobhan F. Cox; Rory Doherty; Sherry Palmer; Ulrich Ofterdinger; Jennifer M. McKinley (Environmental Geochemistry and Health, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Decisional Support throughout the Cancer Journey for Older Women Diagnosed with Early Stage Breast Cancer: A Single Institutional Study - Roseanna Presutti; Laura D’Alimonte; Merrylee McGuffin; Hanbert Chen; Edward Chow; Jean-Philippe Pignol; Lisa Di Prospero; Mary Doherty; Alex Kiss; Jennifer Wong; Justin Lee; Stanley Liu; et al. (Journal of Cancer Education, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Sun exposure and risk of epithelial ovarian cancer - Clara Bodelon; Kara L. Cushing-Haugen; Kristine G. Wicklund; Jennifer A. Doherty; Mary Anne Rossing (Cancer Causes & Control, 2012)

Long-term use of continuous-combined estrogen-progestin hormone therapy and risk of endometrial cancer - Amanda I. Phipps; Jennifer A. Doherty; Lynda F. Voigt; Deirdre A. Hill; Shirley A. A. Beresford; Mary Anne Rossing; Chu Chen; Noel S. Weiss (Cancer Causes & Control, 2011)

Chromosome 15q24-25.1 variants, diet, and lung cancer susceptibility in cigarette smokers - Lori C. Sakoda; Melissa M. Loomis; Jennifer A. Doherty; Marian L. Neuhouser; Matt J. Barnett; Mark D. Thornquist; Noel S. Weiss; Gary E. Goodman; Chu Chen (Cancer Causes & Control, 2011)

Recreational physical activity and risk of epithelial ovarian cancer - Mary Anne Rossing; Kara L. Cushing-Haugen; Kristine G. Wicklund; Jennifer A. Doherty; Noel S. Weiss (Cancer Causes & Control, 2010)

Maximizing resources to study an uncommon cancer: E2C2—Epidemiology of Endometrial Cancer Consortium - Sara H. Olson; Chu Chen; Immaculata De Vivo; Jennifer A. Doherty; Virginia Hartmuller; Pamela L. Horn-Ross; James V. Lacey; Shannon M. Lynch; Leah Sansbury; V. Wendy Setiawan; Leo J. Schouten; Xiao Ou Shu (Cancer Causes & Control, 2009)

Postglacial vegetation and climate dynamics in the Seymour‐Belize Inlet Complex, central coastal British Columbia, Canada: palynological evidence from Tiny Lake - Jennifer M. Galloway; Christine T. Doherty; R. Timothy Patterson; Helen M. Roe (Journal of Quaternary Science, 2009)
A pollen‐based study from Tiny Lake in the Seymour‐Belize Inlet Complex of central coastal British Columbia, Canada, permits an evaluation of the dynamic response of coastal temperate rainforests to postglacial climate change. Open Pinus parklands grew at the site during the early Lateglacial when the climate was cool and dry, but more humid conditions in the later phases of the Lateglacial permitted mesophytic conifers to colonise the region. Early Holocene conditions were warmer than present and a successional mosaic of Tsuga heterophylla and Alnus occurred at Tiny Lake. Climate cooling and moistening at 8740 ± 70 14 C a BP initiated the development of closed, late successional T. heterophylla –Cupressaceae forests, which achieved modern character after 6860 ± 50 14 C a BP, when a temperate and very wet climate became established. The onset of early Holocene climate cooling and moistening at Tiny Lake may have preceded change at more southern locations, including within the Seymour‐Belize Inlet Complex, on a meso‐ to synoptic scale. This would suggest that an early Holocene intensification of the Aleutian Low pressure system was an important influence on forest dynamics in the Seymour‐Belize Inlet Complex and that the study region was located near the southern extent of immediate influence of this semi‐permanent air mass. Copyright © 2008 John Wiley & Sons, Ltd.

Risk of epithelial ovarian cancer in relation to benign ovarian conditions and ovarian surgery - Mary Anne Rossing; Kara L. Cushing-Haugen; Kristine G. Wicklund; Jennifer A. Doherty; Noel S. Weiss (Cancer Causes & Control, 2008)

Physical map of two tammar wallaby chromosomes: A strategy for mapping in non-model mammals - Janine E. Deakin; Edda Koina; Paul D. Waters; Ruth Doherty; Vidushi S. Patel; Margaret L. Delbridge; Bianca Dobson; James Fong; Yanqiu Hu; Cecilia van den Hurk; Andrew J. Pask; Geoff Shaw; et al. (Chromosome Research, 2008)

Multi-proxy evidence of postglacial climate and environmental change at Two Frog Lake, central mainland coast of British Columbia, Canada - Jennifer M. Galloway; R. Timothy Patterson; Christine T. Doherty; Helen M. Roe (Journal of Paleolimnology, 2007)

Endometrial cancer risk in estrogen users after switching to estrogen–progestin therapy - Jessica Chubak; Jennifer A. Doherty; Kara L. Cushing-Haugen; Lynda F. Voigt; Babette S. Saltzman; Deirdre A. Hill; Shirley A. A. Beresford; Noel S. Weiss (Cancer Causes & Control, 2007)

Proteomic analysis of Rac1 transgenic mice displaying dilated cardiomyopathy reveals an increase in creatine kinase M-chain protein abundance - Nina Buscemi; Amanda Doherty-Kirby; Mark A. Sussman; Gilles Lajoie; Jennifer E. Van Eyk (Molecular and Cellular Biochemistry, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)